UMPAN BALIK MODEL PEMBELAJARAN PADA MATERI MEMBUAT POLA BUSANA - NI KETUT WIDIARTINI (PROGRAM STUDI PENELITIAN DAN EVALUASI PENDIDIKAN, 2012)
The purpose of this study is to find out the effect of the feedback and learning models toward the students’ achievement on dress pattern making by controlling the students’ artistic talent of class X of the State Vocation Schools in Denpasar Bali. This research is 2 x 2 Experimental Design Factorial. The samples were taken based on the Multistage Random Sampling with 80 students. This study applied the analysis of covariance (ANCOVA). The results, after controlling the students’ artistic talent, are as follow: (1) the achievement in dress pattern making for the students who were given the feedback of the formative test immediately after the test given is higher than those who were given the formative test feedback delayed, (2) the achievement in dress pattern making for the students who were given the cooperative learning model is higher than those who were given the conventional learning model, (3) there was an effect on the interaction between the formative test feedback and the learning models towards the students’ achievement in dress pattern making, (4) the students who were given the formative test feedback immediately after the test given and were taught by using CO-Op cooperative learning model is higher than those who were taught by using conventional teaching model, (5) the students who were given the formative test feedback delayed after the test given and were taught by using CO-Op Cooperative Learning Model is lower than those who were taught by using conventional teaching model, (6) the students who were taught by using the Co-Op cooperative learning model and were given the formative test feedback immediately after the test given show higher achievement in the dress pattern making than those who were given the formative test feedback delayed, and (7) the students who were taught by using the conventional learning model and were given the feedback immediately after the test given show lower achievement in the dress pattern making than those who were given the feedback delayed after controlling the artistic talent. Based on the research findings, it is recommended to the teachers of the state vocational school that: to improve the students achievement in dress pattern making, the teachers need to use the formative tests feedback and learning models correctly and carefully.